Detection of HPV-16 DNA by PCR in histologically cancer free lymph nodes from patients with cervical cancer. Issue 11 (November 1997) - Baay, M F; Koudstaal, J; Hollema, H; Duk, J M; Burger, M P; Quint, W G; Stolz, E; Herbrink, P
Abstract : The prognostic value of detection of human papillomavirus (HPV) type 16 DNA in histologically cancer free lymph nodes was assessed in left obturator lymph nodes from cervical cancer patients with HPV-16 positive primary tumours. HPV-16 DNA was detected by polymerase chain reaction in 12 of 35 patients with histologically cancer free lymph nodes. Of these 12 patients, only one developed a recurrence, suggesting HPV-16 DNA detection in cancer free lymph nodes has no prognostic value.